Body physique, physical ability and physical training of elite rhythmic gymnasts of China - Qi, J.; Liu, R.; Diao, Z. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: This study examines the physique, physical ability and training of elite rhythmic gymnasts in China to explore the relationship between these variables with the aim of providing a theoretical foundation for the training of rhythmic gymnasts. Methods Twenty elite rhythmic gymnasts from the Chinese National Rhythmic Gymnastics Team were selected for the study. Body physique index and physical ability index for elite rhythmic gymnasts were measured with Sysmex Kx-21 cell counting equipment. A microplate reader and Inbody 3.0 body composition equipment were used to collect the data.